Changing funding arrangements and the production of scientific knowledge: introduction to the special issue - Gläser, Jochen; Serrano-Velarde, Kathia (Minerva, 2018)
With this special issue, we would like to promote research on changes in the funding of the sciences, social sciences, and humanities. Since funding secures the livelihood of researchers and the means to do research, it is an indispensable condition for almost all research; as funding arrangements are undergoing dramatic changes, we think it timely to renew the science studies community’s efforts to understand the funding of research. Changes in the governance of science have garnered considerable attention from science studies and higher education research; however, the impact of these changes on the conduct and content of research has not received sufficient attention, and theoretical insights into the connections between funding practices and research practices are few and far between. The aim of this special issue is to contribute to our theoretical understanding of the changing nature of research funding and its impact on the production of scientific knowledge. More specifically, we are interested in the interplay between funding and research practices: What is the impact of institutionalised funding arrangements on the production of scientific knowledge?
Published online: 29 January 2018
Gesehen am 28.06.2018